HUBUNGAN DUKUNGAN ORANG TUA DENGAN KARAKTER TANGGUNGJAWAB SISWA KELAS IIIB MADRASAH IBTIDAIYAH - Oktaviana, Kharisma; Purnanto, Arif Wiyat; Rahmawati, Puji; Afriyanti, Afriyanti (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The aim of the research was to determine the relationship between parents and the character of responsibility in class IIIB students at MI An Nuur Cahaya Umat.The research method used is quantitative with a correlation research type approach. The research population was 17 class IIIB students at MI An Nuur Cahaya Umat. The independent variable is parental support, while the dependent variable is the character of responsibility. The data collection method is in the form of a questionnaire guided by a specific scale. The data analysis technique uses Pearson Porduct moment analysis from Karl Person with the simple help of IBM SPSS 26. The research was carried out at MI An Nuur Cahaya Umat in August-November 2023.The results of the research show that based on the calculation results regarding the relationship between two variables, namely in the parametric technique with paired sample t with a significance result of (0.314) in the insignificant category and a Pearson correlation score of (-0.260) in the weakly correlated category. So the results of this study do not correlate between the relationship between parental support and the character of responsibility. So it can be concluded that the higher or too pampered the support given by parents to their children, the lower the student's responsible character will be. On the other hand, if the support provided by parents is low or does not pamper the child too much, the child will have a good level of responsible character.